2015
DOI: 10.1016/j.tcb.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Breaking bad: R-loops and genome integrity

Abstract: R-loops, nucleic acid structures consisting of an RNA-DNA hybrid and displaced single-stranded DNA, are ubiquitous in organisms from bacteria to mammals. First described in bacteria where they initiate DNA replication, it now appears that R-loops regulate diverse cellular processes such as gene expression, immunoglobulin class switching and DNA repair. Changes in R-loop regulation induce DNA damage and genome instability, and recently it was shown that R-loops are associated with neurodegenerative disorders. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
299
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(307 citation statements)
references
References 69 publications
7
299
1
Order By: Relevance
“…It is critical to remove excessive R-loops in a timeand space-dependent manner to avoid its catastrophic outcomes [11,13]. This can be achieved by either ribonucleases or helicases.…”
Section: Ribonucleases and Helicasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is critical to remove excessive R-loops in a timeand space-dependent manner to avoid its catastrophic outcomes [11,13]. This can be achieved by either ribonucleases or helicases.…”
Section: Ribonucleases and Helicasesmentioning
confidence: 99%
“…They are involved not only in transcriptional regulation and replication, but also in genomic instability, class-switch recombination in B cells, and DNA damage and repair. These areas of R-loop research have been extensively reviewed recently [1,[10][11][12][13]. Our review focuses on the role of R-loops as an emerging regulator of chromatin dynamics, highlighting the epigenetic interplay of chromatin with this unique DNA structure.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-DNA hybrids may benefit cell physiology, as shown in some cases of transcription initiation and termination, mitochondrial DNA replication, or immunoglobulin class switching . However, RNA-DNA hybrids may also have a strong impact on genome instability, as shown in cells defective in specific mRNP assembly factors such as the THO complex or the SRSF1 RNA-binding protein, topoisomerase I, RNA-DNA helicases, or RNase H, a ribonuclease that specifically degrades the RNA moiety of RNA-DNA hybrids (Santos-Pereira and Aguilera 2015; Sollier and Cimprich 2015). Accumulating evidence indicates that most of this genetic instability is due to the ability of R loops to stall the progression of the replication fork, leading to its collapse (García-Muse and Aguilera 2016).…”
mentioning
confidence: 99%
“…Indeed, the BRCA2 DBD associates with the deleted in split hand/split foot 1 (DSS1) protein (Marston et al 1999), an interaction that is critical not only for HR-mediated DSB repair but also for BRCA2 ability to limit the accumulation of R-loops, a nucleic acid structure composed of an RNA:DNA hybrid and a displaced ssDNA (Sollier & Cimprich 2015). Initial studies showed that DSS1 depletion results in the persistence of RAD51 foci at DSBs (Gudmundsdottir et al 2004) and reduces BRCA2 protein levels (Li et al 2006), but failed to define a clear role for DSS1 in HR.…”
Section: :10mentioning
confidence: 99%
“…In normal cells, R-loops often formed at gene promoters and terminators, and their life time is regulated by RNAse H1, which degrades RNA:DNA hybrids, and by putative helicases (Aquarius Intron-Binding Spliceosomal Factor (AQR) and senataxin (SETX)), which specifically unwind R-loops (Sollier & Cimprich 2015). Although these loops have an important role in the regulation of gene expression and immunoglobulin class switching (reviewed in Sollier & Cimprich (2015)), their uncontrolled accumulation impedes the progression of replication forks and creates genomic instability. R-loop-linked genomic instability is particularly exacerbated in BRCA1/2 tumors cells as well as in cells isolated from FA patients (Kee & D'Andrea 2012, Hatchi et al 2015.…”
Section: Brca2 Safeguards the Integrity Of Dna Against Specific Seconmentioning
confidence: 99%